Determinants of Cesarean Section Deliveries in Public Hospitals of Addis Ababa, Ethiopia, 2018/19: A Case-Control Study - Areaya Gebreegziabher Hailu; Tsegaye Kebede Fanta; Fissaha Tekulu Welay; Natnael Etsay Assefa; Surafel Aregawi Hadera; Gebrekiros Aregawi Gebremeskel; Hagos Weldeslassie Gebremedhin; Guesh Gebreayezgi Asefa (Obstetrics and Gynecology International)
Objective. The objective of this study was to assess the determinants of cesarean section deliveries in public hospitals of Addis Ababa, Ethiopia, 2019. Method. A hospital-based unmatched case-control study was conducted to study 780 (260 cases and 520 controls) women who delivered in public hospitals of Addis Ababa from August 22 to September 20, 2019. The cases were all mothers who delivered through caesarean section, and controls were all mothers who delivered vaginally in the same time in the study area. Data were collected from the randomly selected women and looking into their cards. Data were entered on EpiData 3.1 and exported to SPSS version 20 for cleaning and analyzing. Binary logistic regression and AOR with 95% CI were used to assess the determinants of caesarean section. Results. Majority of the study participants were in the age category 20–34 years. Nearly more than 1/3rd of the participants (32.7% cases and 34.6% controls) have attended primary school. Most of the cases 217 (83.5%) and few of the controls 21 (4%) possess previous caesarean section. One hundred three (52.3%) of the cases and 329 (63.6%) controls were multi-parous. Previous caesarean delivery (AOR = 6.93, 95% CI; (3.39, 14.16)), singleton pregnancy (AOR = 0.34, 95% CI; (0.12, 0.83)), birth weight less than 2500 gm (AOR = 0.29, 95% CI; (0.18, 0.92)), birth weight greater than 4000 gm (AOR = 16.15 (8.22, 31.74)), completely documented partograph (AOR = 0.13, 95% CI; (0.078, 0.23)), and pregnancy-induced hypertension (AOR = 2.44, 95% CI; (1.46, 4.08)) were significant determinants of caesarean delivery in this study. Conclusion. Previous caesarean section, number of delivery, birth weight, partograph documentation, and pregnancy-induced hypertension had significant association with caesarean section delivery in this study.